Prediction of carcass characteristics of discarded Pelibuey ewes by ultrasound measurements - Alfonso J. Chay-Canul; Juan José Pineda Rodriguez; Jaime Olivares-Pérez; Francisco G. Ríos-Rincón; Ricardo García-Herrera; Ángel T. Piñeiro-Vázquez; Fernando Casanova-Lugo (Revista Mexicana de Ciencias Pecuarias, 2019)
The objective ofpresent study was to predict the carcass characteristics of 28 discarded Pelibuey ewes (41.01 ± 8.43 kg) using ultrasonography.The ultrasonic measurements of fat thickness (FT), area, (LDA), depth (DLD) and width (WLD) of the Longissimus dorsi, between the 12thand 13ththoracic vertebra and between the 3rdand 4thlumbar vertebra, were performed 24 h before slaughter. At the slaughter, hot carcass, internal organs and internal fat were weighed. The carcasses were divided in two half, refrigerated (1°C; 24 h) and the chilled carcass were weighed. Then were dissected and weighed in the main tissues. With the data it was calculated the correlation coefficients between the variables and their relationships were estimated using regression models. It was observed that the ultrasonic measurements of thoracic and lumbar backfat thickness had a positive r2 that ranged from 0.51 to 0.66 (P<0.001) for prediction of the carcass weights; and an r2from 0.44 to 0.57 (P<0.001) to predict the carcass muscle quantity.It is possible to use the measurements of ultrasound as a tool for the evaluation of carcass characteristics indiscarded Pelibuey ewes and it is possible to predict the carcass weights and edible tissues.